2021
DOI: 10.1007/s40629-021-00192-4
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability, course and follow-up of specific immunotherapy using a modified ultra-rush procedure in children and adolescents with insect venom allergy

Abstract: Summary Background Specific immunotherapy with insect venom (hymenoptera venom (HG)-AIT) is an effective and the only causal treatment for patients with systemic reactions due to IgE-mediated insect venom allergy. The present study investigated the quality of care after bee and wasp venom allergy, the tolerability of modified ultra-rush immunotherapy and the course after the conclusion of maintenance therapy in children and adolescents. Studies on the quality of life of children wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…As suggested during the development of the VQLQ and later shown in another study, the impact on HRQL differs between honeybee‐allergic beekeepers and non‐beekeepers but the impact on HRQL of honeybee‐allergic non‐beekeepers is comparable to the impact perceived by patients allergic to vespid venom 65,71 . Without distinguishing between the beekeeper‐status, some 70 but not all studies 69,72 observed a lower impairment of HRQL in bee‐venom allergic patients compared to those allergic to wasp venom.…”
Section: Hymenoptera Venommentioning
confidence: 77%
See 4 more Smart Citations
“…As suggested during the development of the VQLQ and later shown in another study, the impact on HRQL differs between honeybee‐allergic beekeepers and non‐beekeepers but the impact on HRQL of honeybee‐allergic non‐beekeepers is comparable to the impact perceived by patients allergic to vespid venom 65,71 . Without distinguishing between the beekeeper‐status, some 70 but not all studies 69,72 observed a lower impairment of HRQL in bee‐venom allergic patients compared to those allergic to wasp venom.…”
Section: Hymenoptera Venommentioning
confidence: 77%
“…With the use of CHVAQoLS in Polish children, a higher anxiety in girls within the group of dermal reactors was shown, but higher levels of anxiety in boys than girls with grade II reactions were observed, 4 while other studies did not find any significant differences between girls and boys 69 . A significant association between the severity of the anaphylactic reaction (Mueller's grade IV compared to grade III) and anxiety was reported, 5 but not confirmed by others 69 .…”
Section: Hymenoptera Venommentioning
confidence: 82%
See 3 more Smart Citations